Isolation and Screening of Bacterial Isolates in UTI Patients in Different age and Gender Groups in Namakkal District, Tamil Nadu - Anusha SU, Sundar SK, Murugan Manavalan (Journal of Applied Pharmaceutical Science, 2014)
Approximately 1 in 3 women will require antimicrobial treatment for a urinary tract infection (UTI). Forty to fifty percentage of the woman will have a UTI before the age of twenty four during their life time. UTI’S in male patients are rare but once infected considered to be complicated. Infection of urinary tract is amongst the most common bacterial infections that prompt patient’s to seek medical advice second only to infection of respiratory tract In the present study, the isolation of urinary tract infecting pathogens from patients of different gender and age group revealed that Escherichia coli was the dominant isolate followed by Klebsiella, Enterobacter, Pseudomonas, Proteus, Acinetobacter, and Staphylococcus aureus.
Keywords: Urinary tract infections, Gender, E.coli.